Enhanced anaerobic co-metabolism of coal gasification wastewater via the assistance of zero-valent iron. (April 2021) - Li, Yajie; Liu, Lingyu; Wang, Qingshui; Wu, Jiazi; Liu, Tonghui; Liu, Hongbo; Hong, Yaoliang; Huang, Tianyin
Graphical abstract: Highlights: New insights to anaerobic co-metabolism of CGW with the assistance of ZVI were investigated. Optimum addition dosages of ZVI (1 g/L) and glucose concentration of 1500 mg COD/L were obtained. Co-metabolic environment by ZVI was conducive to improve the growth and activity of methanogens. Microbial cultivation model of ZVI + glucose can increase the number of microbial species. Abstract: Coal gasification wastewater (CGW) contains high-concentration phenols which lead to poor anaerobic biodegradability and low resource utilization. Anaerobic co-substrate can provide abundant electron donor while zero-valent iron (ZVI) can enhance the methanogenesis by promoting electron transfer. Hence, new insights to anaerobic co-metabolism of CGW with the assistance of ZVI were investigated. Batch tests showed that when ZVI dosage was 1.0 g/L and glucose was used as the co-substrate with concentration of 1500 mg COD/L, the COD concentration in CGW decreased from 3644 to 750 mg/L after 6 days anaerobic digestion, obtaining COD removal rate of about 79.4%. The average total phenol (TP) concentration decreased from 509 mg/L on day 1 to almost 0 mg/L on day 3. The cumulative methane production for 6 days was about 245 mL. During the 90-day long-term operation, the average removal rates of COD and total phenol were about 34% respectively and the average methane production was only 13 mL/day with no ZVI addition. However, with the addition of 1 g/L ZVI in the system, the average removal rates of COD and total phenol rose to 65.3% respectively and the average methane production rose to 106.4 mL/day. Furthermore, with the glucose (COD = 1500 mg/L) continued to add in the influent, the average COD and TP removal rates rose to 76.2% and 73.5% respectively and the average methane production promoted to 447.6 mL/day. The Venn analysis indicated that the microbial cultivation method of ZVI and glucose additions can increase the number of microbial species.